Correlation between Erythropoietin Resistance Index and Mortality in Regular Hemodialysis Patients at Haji Adam Malik General Hospital Medan - Nasution, Fakhri Amin; Nasution, Alwi Thamrin; Nasution, Feldy G (Journal of Endocrinology, Tropical Medicine, and Infectious Disease (JETROMI), 2023)
Introduction: One of the functions of the kidneys is the production of erythropoietin, a signaling molecule that stimulates the production of red blood cells, in response to reduced oxygen levels in the blood. In chronic kidney disease, there is a disturbance in the production of erythropoietin. Several previous studies have linked the index of erythropoietin resistance to mortality in patients with chronic kidney disease. The study aimed to correlate between erythropoietin resistance index (ERI) and Mortality in regular hemodialysis patients. Method: Observational analytic study with a cross-sectional method to assess the relationship between ERI and mortality in all regular hemodialysis patients at H Adam Malik Medan. The ERI was used to evaluate erythropoietin EPO by comparing the dose of EPO to the hemoglobin level. The data were tested statistically with the Chi-Square method. Results: The average study subjects suffered from anemia with Hb levels of 8.21 g/dL, serum iron levels of 63.22 mcg/dL, and increased total iron-binding capacity (TIBC) levels with an average value of 190.2 mcg/dL, low ferritin levels of 195.59 mcg/L and serum transferrin (TSAT) 19.2%, and of 2.94 g/dL. Albumin levels, transferrin saturation, and ERI were associated with the mortality rate of patients undergoing regular hemodialysis (p=0.021; p=0.011; p=0.012). Conclusion: There is a relationship between the index of erythropoietin resistance and the mortality rate of patients undergoing regular hemodialysis